An updated chronology for Umbeli Belli and its implications for the Middle and Later Stone Ages - Chantal Tribolo; Nicholas J. Conard; Matthias Blessing; Gregor D. Bader (South African Journal of Science, 2024)
We present a series of 12 OSL/IRSL dates that revise and complete the chronology of the important Middle (MSA) and Later Stone Age (LSA) site Umbeli Belli in KwaZulu-Natal, South Africa. These dates shift the previous radiometric ages thousands of years older than earlier measurements and play a key role in revising the cultural stratigraphy of KwaZulu-Natal. We also discuss how these dates bring the chrono- and cultural stratigraphy of southern Africa into clearer focus. The Robberg sequence of Umbeli Belli is now firmly dated to 21 ± 2 ka, whereas the preceding Early LSA assemblage dates to ~32 ka, representing one of the earliest dates for this cultural expression in the broader region. The final MSA assemblages from Layer 7 to 9 now date to between 35 ka and 40 ka, overlapping more tightly with comparable assemblages from Sibhudu, Umhlatuzana and other sites. Layer 10, which was previously also assigned to the final MSA, now dates to ~47–54 ka, placing the assemblage within the temporal range of the Late MSA. The new dates provide a good explanation for the clear differences in material culture between Layer 10 and the younger layers. We also present two new ages for the deeper horizons 11b and 12 at Umbeli Belli, dating to 76 ± 9 ka and 80 ± 9 ka, respectively.